Non-refoulement under the European Convention on Human Rights and the UN Convention Against Torture: the assessment of individual complaints by the European Court of Human Rights under Article 3 ECHR and the United Nations Committee Against Torture under Article 3 CAT - Weck, Fanny de (International refugee law series, 2017)
Introduction -- The individual complaint mechanisms in light of the non-refoulement principle -- The nature of the harm triggering the application of the non-refoulement principle under the ECHR and the CAT -- Assessment of risk -- Summary and concluding remarks